Improvement of soil health and crop production through utilization of organic wastes: A sustainable approach - R.Y. Hiranmai; Ajay Neeraj; Parul Vats (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Solid organic waste is a major environmental issue in various parts of the world. Proper management techniques for disposing of such wastes can reduce health issues as well as contamination of the environment. Modern scientific techniques in conjugation with traditional practices can manage biowaste in an efficient, economical, and sustainable manner. This present review highlights the possibilities of utilizing biowastes from various sources for the enhancement of soil fertility, residue management, crop growth and higher yields. Methodology: The article is prepared from secondary materials i.e. research and review articles published in different journals. The review of literature from these articles in terms of soil quality, salinity, impact of salinity on crop production and possibilities to reclamate saline soil to improve productivity of soil were systematically carried out. A summary of the present work was developed using the following approach. Result: Various management practices, in-situ and ex-situ techniques help reduce biowastes and transform them into useful nutrients that could be applied to soil for alleviating the nutritional deficiency in saline/sodic soil. Composting using microbes and earthworms has been traditionally practiced for reducing/converting waste into compost and applying them to agricultural fields to improve soil fertility and crop productivity. Conclusion: Using waste management techniques and converting biowaste into manure for enhancing agricultural productivity provides sustainable agriculture practices in addition to pollution reduction.